Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer: To solve the quadratic equation \(3x^2 - 8x - 3 = 0\), we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In this equation, \(a = 3\), \(b = -8\), and \(c = -3\). Plugging these values into the quadratic formula gives:
\[ x = \frac{-(-8) \pm \sqrt{(-8)^2 - 4 \cdot 3 \cdot (-3)}}{2 \cdot 3} \]
\[ x = \frac{8 \pm \sqrt{64 + 36}}{6} \]
\[ x = \frac{8 \pm \sqrt{100}}{6} \]
\[ x = \frac{8 \pm 10}{6} \]
This results in two solutions:
1. \( x = \frac{8 + 10}{6} = \frac{18}{6} = 3 \)
2. \( x = \frac{8 - 10}{6} = \frac{-2}{6} = -\frac{1}{3} \)
Thus, the solutions to the quadratic equation \(3x^2 - 8x - 3 = 0\) are:
\[ x = 3 \quad \text{and} \quad x = -\frac{1}{3} \]
Step-by-step explanation:
:)
Answer:
x = 3, x = -1/3
Step-by-step explanation:
3x² - 8x - 3 = 0
Using Factorization method,
3x² -9x + x - 3 = 0
3x(x - 3) + 1(x - 3) = 0
(x - 3)(3x + 1) = 0
x - 3 = 0, 3x + 1 = 0
x = 3, 3x = -1
x = 3, x = - 1/3
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.